Last Word on Viewpoint: Hoping for the best, prepared for the worst—can we perform remote data collection in sport sciences? - Souza, H. L. R.; Bernardes, B. P.; dos Prazeres, E. O.; Arriel, R. A.; Meireles, A.; Camilo, G. B.; Mota, G. R. (Journal of Applied Physiology, 2022)
We read the commentaries from several authors and research groups (1) regarding our recent Viewpoint on remote data collection in sport sciences (2) with great enthusiasm and, considering the remarkable offered perspectives we present a final word.